The Motivational Effects of Mission Matching: A Lab‐Experimental Test of a Moderated Mediation Model. (27th January 2016) - Smith, Jason
Abstract: Scholarly literature finds positive motivational effects of matching workers and missions. However, the psychological mechanisms behind this matching effect have not been explored. This article develops and tests a moderated mediation model of mission matching in which meaningfulness serves as an intervening mechanism that explains the association between mission matching and effort. It also considers how individual differences in prosocial motivation influence the intervening role of meaningfulness. Using a real‐effort laboratory experiment with monetary incentives, the article shows that matched subjects exert more effort than mismatched subjects, that this effect is mediated by increases in meaningfulness, that prosociality moderates the effect of a match on meaningfulness, and that the indirect effect of a match on effort through increases in meaningfulness varies as a function of prosociality. These results contribute to a more nuanced understanding of mission matching and suggest that matching may be particularly important for certain types of workers .